Characterizing the microstructure of Arctica islandica shells using NanoSIMS and EBSD - Karney, G; Butler, P; Speller, S; Scourse, J; Richardson, C; Schroeder, M; Hughes, G; Czernuszka, J; Grovenor, C (2012)
The bivalve mollusc Arctica islandica has received considerable attention in recent years because of its potential as an archive of marine palaeoclimate, based on its annually resolved incremental shell growth, longevity, and synchronous growth within populations. The robust interpretation of the archive depends on a detailed understanding of the shell formation process, and this in turn requires a reliable understanding of the shell microstructure. Research into this aspect, however, has so far been relatively limited. This study uses secondary ion mass spectrometry (NanoSIMS) to examine the compositions of the two annually formed growth increments, i.e., a narrow band of relatively slow growth referred to as growth increment I (GI I) and a usually wider accretion called growth increment II (GI II). High resolution composition maps are presented which clearly show lower concentrations of the organic ions 12C 14N - and 32S - in GI I relative to GI II. This is consistent with the growth of larger crystallites in GI I, which is clearly demonstrated using a novel analysis method involving focused ion beam (FIB) milling. Electron backscatter diffraction (EBSD) analysis is also presented, and demonstrates that the orientation of the aragonite c-axis is the same in both GI I and GI II, and that the a- and b-axes assume preferred orientations consistent with the known angle of twinning in aragonite. By analyzing individual crystallites it is deduced that the (001) plane is likely to be the mineralizing face in GI I, and that the (011) and (102) planes are low energy interfaces in GI II. Copyright 2012 by the American Geophysical Union.